Reach : 40 Black men speak on living, leading, and succeeding / edited by Ben Jealous and Trabian Shorters ; foreword by Russell Simmons. - Jealous, Benjamin Todd, 1973-; Shorters, Trabian; Simmons, Russell; Shorters, Trabian. (Atria Paperback, a division of Simon & Schuster, Inc., 2015)
In this timely and important collection of personal essays, black men from all walks of life share their inspiring stories and how each, in his own way, became a source of hope for his community and country.